PENDIDIKAN AGAMA NON FORMAL KAITANNYA DENGAN PEMBINAAN REMAJA - Nasution, Sahadir (AIN Padangsidimpuan, 2013)
AbstractInformal religion education seems to be a conscious, structured and programmed education. It is performed beyond religion or public education institution. More over, Islamic education gives students science theory and practice for life.In conclusion, both science theory and practice of Islamic education should be revised and developed into goodness for future human’s needs.Key words : Informal religion education and adolescent.